Prostaglandin E inhibition of T-lymphocyte colony formation: a possible mechanism of monocyte modulation of clonal expansion. - Bockman, R S (1979)
Prostaglandin and monocyte modulation of a T-lymphocyte cell capable of undergoing clonal expansion was studied. Circulating human mononuclear cells were isolated by density centrifugation. After 24 h in culture with phytohemagglutinin present, the cells were mixed with 0.3% agar and overlayed onto a 0.5% agar layer that contained media and phytohemagglutinin. At day 6, colonies that contained greater than 50 cells were counted. These colonies represented clonal prolifertion of a phytohemagglutinin-responsive T-lymphocyte precursor. This responder cell accounted for less than 0.3% of the starting cell population. Colonies were comprised of cells which, when isolated, formed E rosettes. These colony cells could be shown to have helper or suppressor function as measured by their ability to promote or inhibit immunoglobulin synthesis. By these latter criteria the colony cells were considered to be mature T lymphocytes. The addition of prostaglandin E to the cultures demonstrated a linear, r = 0.82, dose-dependent inhibition of colony formation with a 50% point of inhibition (I50) = 0.18 muM. Low numbers of normal monocytes when added to the cultures mimicked the effect of synthetic prostaglandin E2. A highly significant correlation could be shown for endogenous prostaglandin E levels and colony counts. It appears that monocytes through their synthesis of prostaglandin E2 can restrict the clonal expansion of a circulating T-lymphocyte precursor.